Implikasi Psikologis Bagi Penghafal Al-Qur’an - Yusron Masduki (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2018)
The wisdom of memorizing the Koran will be won, whoever recites the Qur'an, learns, and practices, is applied to his parents' crown of light on the Day of Resurrection. The light is like sunlight and both parents are dressed in two glorious robes that were never found in the world. The virtue of memorizing the Qur'an: first, the Qur'an as a giver of intercession for the reader, understanding and practicing; secondly, the memorizers of the Qur'an have been promised by Allah SWT, thirdly, the Qur'an becomes Hujjah / defender for the reader and as a guardian of the torrent of hell fire. The special Qur'an reader memorizing the Qur'an quality and quantity of higher reading, will be with the angel always protect and invite to the good. As for psychological implications for the first Qur'an memorizers, as a drug distracted, anxious and anxious; secondly, memorizing the Qur'an to gain peace of mind, intelligence and boost learning achievement; third, the memorization of the Qur'an can reduce juvenile delinquency and tawuran; the memorization of the Qur'an will be highly rewarded by Allah and His Messenger; memorizing the Qur'an as a cure for anyone who reads and memorizes. Hikmahnya hafal al-Quran akan diperoleh kemenangan, barang siapa membaca al-Qur’an, mempelajari, dan mengamalkan, dipakaikan kepada orang tuanya mahkota dari cahaya pada hari kiamat. Cahayanya seperti cahaya matahari dan kedua orang tuanya dipakaikan dua jubah kemuliaan yang tidak pernah didapatkan di dunia. Keutamaan menghafal al-Qur’an: pertama, al-Qur’an sebagai pemberi syafa’at pada bagi pembaca, memahami dan mengamalkan; kedua, penghafal al-Qur’an telah dijanjikan derajatnya oleh Allah SWT, ketiga, al-Qur’an menjadi Hujjah/pembela bagi pembaca dan sebagai pelindung dari adzab api neraka. Pembaca al-Qur’an khusus penghafal al-Qur’an kualitas dan kuantitas bacaan lebih tinggi, akan bersama malaikat selalu melindungi dan mengajak kepada kebaikan. Adapun implikasi secara psikologi bagi penghafal al-Qur’an pertama, sebagai obat galau, cemas dan cemas; kedua, menghafal al-Qur’an untuk memperoleh ketenangan jiwa, kecerdasan dan mendongkrak prestasi belajar; ketiga, penghafal al-Qur’an dapat meredam kenakalan remaja dan tawuran; penghafal al-Qur’an akan mendapat penghargaan yang tinggi di sisi Allah dan Rasul-Nya; menghafal al-Qur’an sebagai obat bagi siapa saja yang membaca dan menghafalkan.